Alumina nanocrystalline ceramic by centrifugal casting. Issue 4 (April 2023) - Li, Yuanyuan; Shen, Bing; Yang, Hongbing; Hu, Guangkuo; Yang, Desheng; Wang, Jun; Dong, Yanhao; Li, Jiangong
Abstract: Centrifugal casting is an established molding method to prepare ceramics with high strength and high reliability and it has been well demonstrated in Al2 O3 . However, it has not yet been applied to Al2 O3 nanocrystalline ceramic with < 100 nm grain size, primarily due to the unavailability of high-quality α -Al2 O3 nanoparticles. In addition, ultrafine nanoparticles may be difficult to cast from the solution unless high-speed ultracentrifuge (e. g., >60, 000 rpm) is used. Here we addressed these two challenges by home-made dispersed α -Al2 O3 nanoparticles with 10 nm average particle size and HCl-assisted casting under a "normal" centrifuge condition and report the first attempt to produce Al2 O3 nanocrystalline ceramic by centrifuge casting and pressureless sintering. The sintering kinetics and microstructure were analyzed, which assists the design of optimal two-step sintering schedule. We showed that dense Al2 O3 nanocrystalline ceramic with 65 nm average grain size and ultra-uniform microstructure (the standard deviation of the grain size distribution to the average grain size is 0.358) can be obtained by two-step sintering at 1175 °C without holding followed by holding at 1025 °C for 20 h. The ultra-uniform microstructure may result from the denser and more uniform packing of particles in the green bodies produced by centrifugal casting. The two-step sintered Al2 O3 nanocrystalline ceramic has a microhardness of 19.9 GPa. The microhardness indicates potential softening (inverse Hall-Petch relationship) of Al2 O3 nanocrystalline ceramic at such a grain size. Highlights: Centrifugal casting of the green bodies from the α -Al2 O3 nanoparticles under a normal centrifuge condition. Al2 O3 ceramic with 65 nm grain size and uniform grain size distribution was prepared by two-step sintering. Centrifugal casting offers uniform nanoparticle packing in the green bodies. Two-step sintered Al2 O3 nanocrystalline ceramic has 19.9 GPa average microhardness.